APPLICATION OF RESONANT CONVERTER IN OZONE GENERATOR MODEL - Mochammad Facta; Zainal Salam; Zolkafle Bin Buntat (Universitas Ahmad Dahlan, 2008)
Ozone is one of the favorable oxidant to use in home appliance and industry as disinfectant for food processing, food storage, odor abatement, groundwater remediation, and drinking water purification. The common and previous technical method for generating ozone uses a high voltage and low frequency. This kind of method has disadvantage of energy efficiency, size and weight. This paper proposed the use power electronics in the inverter resonant circuit to produce alternating current with high frequency. The basic RLC resonance circuit is used for early study to determine resonance frequency for inverter. As the result, the ozone chamber terminal voltage had been achieved for initiation by using resonance frequency.